Reimplantation versus remodelling with ring annuloplasty: comparison of mid-term outcomes after valve-sparing aortic root replacement. (8th February 2018) - Lenoir, Marien; Maesen, Bart; Stevens, Louis-Mathieu; Cartier, Raymond; Demers, Philippe; Poirier, Nancy; Tousch, Michaël; El-Hamamsy, Ismail
Abstract: OBJECTIVES: Remodelling with extra-aortic ring annuloplasty has emerged as an alternative approach to root reimplantation. However, no studies have yet compared outcomes between procedures. The aim of this study was to compare mid-term outcomes in patients undergoing reimplantation versus remodelling with extra-aortic annuloplasty. METHODS: From 2001 to 2017, 142 patients underwent root remodelling with extra-aortic annuloplasty ( n  = 83, 48 ± 13 years) or a reimplantation technique ( n  = 59, 48 ± 12 years) at the Montreal Heart Institute. No differences were observed in the incidence of connective tissue disease (24% vs 29%, P  = 0.9) or preoperative aortic insufficiency ≥3 (37% vs 23%, P  = 0.24). However, in the remodelling group, there were more bicuspid aortic valves (31% vs 9%; P  < 0.01), and the mean preoperative aortic annulus diameter was larger (27.2 ± 3.6 mm vs 25.6 ± 2.4 mm; P  = 0.01). The mean follow-up duration was 3.9 years (100% complete). RESULTS: There were no hospital deaths and 5 late deaths. At 5 years, overall survival was similar in both groups (100%, P  = 0.98). Similarly, 5-year freedom from aortic valve reoperation was equivalent (97 ± 2% in both groups, P  = 0.95). Furthermore, 5-year survival free from aortic insufficiency ≥2 or reoperation was 84 ± 5% in the remodelling with annuloplasty group vs 83 ± 6% in the reimplantation group ( P  = 0.62). The mean annular diameter was 24.3 ± 0.5 mm at 5 years vs 23.6 ± 0.3 mm at discharge in the remodelling group ( P  = 0.28) and 24.4 ± 0.6 mm vs 23.2 ± 0.3 mm, respectively, in the reimplantation group ( P  = 0.1). CONCLUSIONS: Despite a higher prevalence of bicuspid aortic valves and larger aortic annular diameters, mid-term outcomes after remodelling with extra-aortic annuloplasty and reimplantation are comparable. Extra-aortic ring annuloplasty is effective at stabilizing annular dimensions.